204 FRAILTY BUT NOT AGE IS ASSOCIATED WITH IMPAIRED ORTHOSTATIC CEREBRAL OXYGENATION. (18th November 2021) - Pérez-Denia, L; Claffey, P; Byrne, L; Rice, C; Kenny, R A
Abstract: Background: The effects of age and frailty on cerebrovascular function are poorly understood. Here we investigate the hypotheses that aging, and frailty are accompanied by impaired regulation of cerebral oxygenation during standing in a patient population of older adults. Methods: We recruited patients from a national Falls and Syncope service. All patients underwent an active stand test (5–10 min lying, 3 min standing) with continuous monitoring of blood pressure (BP) and heart rate. Tissue saturation index (TSI) was concurrently measured using near-infrared spectroscopy and its recovery measured at 30s after standing. Frailty was assessed as a comorbidity count using a 27-item questionnaire. Robust linear regression was used to investigate the association between TSI, age and frailty in a multivariate model with covariate adjustment, including the concurrent BP values. A p-value <0.05 was considered significant. Results: 304 patients (median(IQR): 71(14) years, 57% females) were recruited. Age was not associated with cerebral oxygenation after standing (β: −0.001 (−0.017 0.015), p = 0.899), even after stratification by sex (males: β: −0.010 (−0.045 0.024), p = 0.558, females: β: 0.000 (−0.017 0.018), p = 0.967). Frailty, was associated with a lower TSI at 30s after standing (β: −0.153 (−0.248–0.058), p = 0.002). After sex stratification, no associations with frailty were observed in males (β: −0.052 (−0.226 0.123), p = 0.557), while frailer females demonstrated a lower TSI at 30 seconds after standing (β: −0.179 (−0.294–0.063), p = 0.003) despite BP correction. Conclusion: Our results suggest alternative mechanisms of cerebral oxygenation regulation independent of blood pressure (and presumably cerebral autoregulation) are involved in frailty related impairments of brain haemodynamics which are also independent of ageing. Such impairments represent novel biomarkers of frailty and represent potentially novel modifiable risk factors (independent of BP management) of hypoperfusion related disorders in clinical ageing.